Endothelial microparticles from acute coronary syndrome patients induce premature coronary artery endothelial cell aging and thrombogenicity: role of the Ang II/AT1 receptor/NADPH oxidase-mediated activation of MAPKs and PI3-Kinase pathways - Abbas, Malak; Rumig, Cordula; Hecker, Markus (Circulation, 2017)
Background:Microparticles (MPs) have emerged as a surrogate marker of endothelial dysfunction and cardiovascular risk. This study examined the potential of MPs from senescent endothelial cells (ECs) or from patients with acute coronary syndrome (ACS) to promote premature EC aging and thrombogenicity. Methods:Primary porcine coronary ECs were isolated from the left circumflex coronary artery. MPs were prepared from ECs and venous blood from patients with ACS (n=30) and from healthy volunteers (n=4) by sequential centrifugation. The level of endothelial senescence was assessed as senescence-associated β-galactosidase activity using flow cytometry, oxidative stress using the redox-sensitive probe dihydroethidium, tissue factor activity using an enzymatic Tenase assay, the level of target protein expression by Western blot analysis, platelet aggregation using an aggregometer, and shear stress using a cone-and-plate viscometer. Results:Senescence, as assessed by senescence-associated β-galactosidase activity, ...